Kontribusi Lingkungan Belajar Terhadap Kemampuan Literasi Teknologi Siswa di SMKN 7 dan 9 Padang - Dayurni, Popi; Rizal, Fahmi; Ambiyar, Ambiyar (Universitas Negeri Padang, 2020)
The problem in this research is the development of technology such as computers and the internet is not used for learning purposes but for things that are not important such as social media and games, the lack of habit of using technology such as computers to support the learning process results in the emergence of computer anxiety (doubt in using computers. from the doubt of using this computer, the motivation of students to use computers effectively will decrease and the learning environment does not support the sustainability of the learning process by utilizing technology to the maximum, then the lack of motivation of students in doing school work using existing technology and the lack of the role of teachers or parents in control the use of technology by students so that technological development is not utilized for the benefit of learning. The purpose of research is to know the learning environment that contributes to the ability n technology literacy of students. This research uses correlational quantitative research. Based on the results of the study it was found that there was a positive and significant contribution to the learning environment towards the ability of students' technology literacy with a contribution percentage of 64.5%.